Characteristics of measured typhoon waves on the central coast of Zhejiang province - Yang, Zhongliang; Ye, Qin; Yang, Bin; Shi, Weiyong; Zhang, Junbiao (Frontiers in Marine Science, 2024)
The risk of typhoon disasters is high in the Zhejiang coastal areas; however, it has been difficult to characterize waves generated by these typhoons, particularly in shallow waters. In this study, the characteristics of nearshore typhoon waves were analyzed using data from 14 typhoon processes from a wave station on the central coast of Zhejiang Province for three consecutive years from 2016 to 2018. According to their paths, these typhoons were divided into landing and non-landing steering types. Wave parameters were evaluated using statistical analyses and linear regression. Variations in wave parameters and spectra are discussed. We obtained several key results: (1) The dominant wave direction was E-SE and the strong wave direction was SE. (2) There were strong correlations between characteristic wave heights and between characteristic periods. (3) Single-peak spectra were dominant, with a frequency of 92.33%. The minimum peak frequency was 0.06–0.1 Hz and the maximum peak period was 17.7 s. The typhoon waves were mainly composed of swells with a frequency of 94.54%. (4) Affected by Typhoon Maria (No. 201808), a maximum wave height of 8.20 m was observed at 04:00 on July 11, 2018. This study provides an important reference for the design of offshore structures and disaster prevention and mitigation.